Kuwait’s Mediation in the Gulf Crisis: Dynamics of Kuwait’s Foreign Policy Approaches - Huzeyfe Altiok (15445460) (2023)
This study examines Kuwaiti mediation in the 2017 Gulf crisis from the perspective of the disputants—mainly Saudi Arabia, the United Arab Emirates, and Qatar—and the mediator—Kuwait. While using qualitative research method such as interviews with the scholars, and discourse analyses, this chapter provides an overview of the Kuwaiti mediation in the Gulf crisis and reconstructs the role of small states in International Relations. Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_35